141k views
1 vote
G(n) = 4nf(n) = -2n + 2Find g(f (4))Type in your number answer at the bottom.

1 Answer

7 votes

-24

Step-by-step explanation

Let


\begin{gathered} g(n)=4n \\ f(n)=-2n+2 \end{gathered}

Step 1

find f(4)


\begin{gathered} f(4)=-2(4)+2 \\ f(4)=-8+2 \\ f(4)=-6 \end{gathered}

Step 2

find g(f(4))


\begin{gathered} g(f(4))=g(-6)=4\cdot-6=-24 \\ g(f(4))=-24 \\ g(f(x))=4(-2n+2)=-8n+8 \\ g(f(4))=-8(4)+8=-32+8=-24 \end{gathered}

I hope this helps you

User Cassidymack
by
5.5k points